Microsatellite markers to identify two species of Tilapiine fish, Oreochromis mossambicus (Peters) and O. niloticus (Linnaeus) - Esterhuyse, M. M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2002.